Incidence and Causes of Early Hospital Readmissions after Cardiac Surgery. One Year Experience at Tertiary Care Hospital, Multan: Early Hospital Readmissions after Cardiac Surgery - Murtaza, Muhammad Sher I; Chaudhary, Muhammad Hamid; Hafeez, Khurram (Pakistan Journal of Health Sciences, 2025)
The increased costs, morbidity, and mortality associated with readmissions after cardiac surgery pose a substantial issue for the healthcare system. Objective: To observe the incidence, causes, and outcome of hospital readmissions within two months of discharge after cardiac surgery. Methods: An observational descriptive cohort study was conducted at Chaudhary Pervaiz Elahi Institute of Cardiology, Multan, Pakistan. From September 2023 to August 2024, 1406 patients undergoing cardiac surgery were observed for readmission in the hospital within two months after discharge. Patients who were operated at other facility and those who admitted after 2month were excluded from the study. Perioperative data, reasons for readmission, and outcomes were recorded and analyzed using SPSS version 25.0. Descriptive statistics were applied to continuous and categorical variables. Results: The incidence rate of readmission was 7.5% (n=106). 85.8% readmissions occurred within 30 days after discharge. Common causes of readmission were anticoagulation-related issues (23.6%), wound infections (21.7%), pleural effusion (15.1%), pericardial effusion (9.4%), and sternal dehiscence (6.6%). Surgical intervention was required in 35.8% of readmitted patients. The mean length of readmission hospital stay was 4 ± 2.80 days. Mortality in readmitted patients was 4.7% (n=5). Conclusions: Nearly every 13th patient needs hospital readmission. Early hospital readmission is most common in patients who needs anticoagulation after valve replacement surgery. Early readmission after cardiac surgery, adversely impacts patient outcomes. Improved anticoagulation management, infection control, and postoperative diuretics, are critical for reducing incidence of hospital readmission